Case – Ex-vivo aneurysm resection, autotransplantation, and aortorenal bypass in a solitary kidney with fibromuscular dysplasia - Sarwal, Gautamn; Brotherhood, Hilary L.; Chedgy, Edmund C.P.; Taylor, David C.; Kavanagh, Alex G. (Canadian Urological Association Journal, 2018)
N/A